Pengembangan Penuntun Praktikum Laju Reaksi Berbasis Green Chemistry Studi pada Peserta Didik Kelas XI IPA MAN Tana Toraja - Amaliah, Maurizka; Anwar, Muhammad; Sudding, Sudding (Chemistry Education Review (CER), 2023)
This study is a development research that aims to develop practicum guidelines of green chemistry-based reaction rate that are valid, practical, and effective. The    research procedure employed the ADDIE development model, which consisted of the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The practicum guidelines was validated by two experts. Then it was tried out in XI IPA 1 class and XI IPA 2 class at MAN Tana Toraja. The results showed that the average level of validity of practicum guidelines of green chemistry-based reaction rate was stated to be very valid and feasible to use. The practicality test includes: (1) the implementation of practicum guide learning is in class XI IPA 1 aspects and the observed criteria are in the perfected category, (2) Student responses show that practicum guides are in the very practical category and (3) The teacher's response to the guide practicum is in the very practical category. In addition, the green chemistry-based reaction rate practicum guide that was developed was effective in terms of, (1) students' learning interest was in the moderate category, (2) Learning outcomes of students in XI IPA 1 class and XI IPA 2 class met the criteria for being effective.